The Case of Charles Taylor from the Perspective of Individual Criminal Responsibility in Crimes Against Humanity - Nur Aliya Rasyidah (International Journal of Law, Environment, and Natural Resources, 2024)
Crimes against humanity are one of the most serious violations of international criminal law, including widespread and systematic acts against civilians, such as murder, sexual slavery and torture. The principle of individual criminal responsibility is applied to ensure that perpetrators, including leaders of a state, can be tried for their actions. The case of Charles Taylor, former President of Liberia, is an important study of how international criminal law prosecutes leaders of states who support crimes against humanity through ad hoc courts. This paper uses a juridical-normative method with a case approach. The results of the study show that the verdict on Charles Taylor confirms the principle that no individual, not even a head of state, is immune from the law. However, the enforcement of international criminal law requires increased cross-country cooperation, strengthening of international judicial institutions, and mechanisms to cut off the funding of armed conflicts, to ensure global justice and human rights protection are better protected.